The influence of cyberloafing to generation z’s productivity: looking at role of creativity as mediating factor - Handi Wijaya Hartanto; Rosaly Franksiska (KINERJA, 2021)
In today's digital era, students are very close to the internet. Today's students are students of the z generation, students who are not free from the internet. They access the internet using gadgets that they can carry anywhere and can access the internet wherever they want, this results in cyberloafing. Cyberloafing is the behavior of using the internet in a learning environment for personal interests that are not related to assignments at school. This can affect the productivity and creativity of students, so this study was conducted with the aim to examine the effect of cyberloafing on productivity, cyberloafing on creativity and creativity on productivity. This type of research is a type of quantitative research using statistical calculations with Structural Equation Modeling (SEM) analysis methods. Using a purposive sampling method, by looking for respondents who meet criteria such as students with a generation of z and also open gadgets to open things that have nothing to do with learning during lecture hours. The results of this study state that cyberloafing has a significant effect on productivity with a probability value of 0.009 0.05, then cyberloafing has a significant effect on creativity with a probability value of 0.026 0.05, then creativity also has a significant effect on productivity with its probability value as big as *** or the value is less than 0.001 0.05 and in this study also gets the results that creativity can mediate the influence of cyberloafing on productivity in student generation z with a coefficient of 0.027. Based on the results of these studies it can be concluded that there is a significant influence between cyberloafing on productivity, cyberloafing on creativity and creativity on productivity and creativity can mediate the influence of cyberloafing on productivity in student generation z.Â